The Influence of Service Performance and Institutional Age on Budgetary Independence with Financial Performance as A Mediating Variable (A Study at The Bendan Regional General Hospital Public Service Agency, Pekalongan City) - Ayu, Farah; Maria Goretti Kentris Indarti (LPPM Universitas Pekalongan, 2025)
The purpose of the study was to test and analyze the independent variables in the form of service performance and agency age on the dependent variable in the form of independence ratio and test the mediation of financial performance in this role at the Regional Public Service Agency (BLUD) of RSUD Bendan Pekalongan City taken in 2018-2023. The population in this study is the annual financial report of the Regional Public Service Agency of Bendan Hospital, Pekalongan City. The sampling method uses purposive sampling method, namely by taking a predetermined sample based on the aims and objectives of the study. The provisions of the sample taken are Notes on Financial Statements (CALK) of the Regional Public Service Agency of the Bendan City Hospital of Pekalongan for the period 2018-2023 which are broken down into monthly data so that the total data obtained is 72. The data collection method uses secondary data. Data analysis using PLS (Partial Least Square) regression analysis. Based on the results of the study, it can be concluded that service performance has no effect on financial performance, agency age has no significant effect on financial performance, service performance has no significant effect on budget independence, agency age has a positive and significant effect on budget independence, financial performance has a positive and significant effect on budget independence, financial performance does not mediate the effect of service performance on the independence ratio, and financial performance mediates the effect of agency age on the independence ratio of BLUD Bendan Hospital Pekalongan City in the period 2018 - 2023 Keywords: service performance, agency age, financial performance, independence ratio, RSUD Kota Pekalongan